Experimental Evaluation of PV Panel Efficiency Using Evaporative Cooling Integrated with Water Spraying (Journal of Engineering, 2023)
In this work, an inventive photovoltaic evaporative cooling (PV/EC) hybrid system was constructed and experimentally investigated. The PV/EC hybrid system has the prosperous advantage of producing electrical energy and cooling the PV panel besides providing cooled-humid air. Two cooling techniques were utilized: backside evaporative cooling (case #1) and combined backside evaporative cooling with a front-side water spray technique (case #2). The water spraying on the front side of the PV panel is intermittent to minimize water and power consumption depending on the PV panel temperature. In addition, two pad thicknesses of 5 cm and 10 cm were investigated at three different water flow rates of 1, 2, and 3 lpm. In Case #1, the evaporative cooling decreased the temperature of the PV panel by about 15 ℃ related to the uncooled PV panel for both pad thicknesses. While case #2 showed a more significant temperature drop for PV panel by about 27 ℃  and 29.7 ℃ for pad thicknesses of 5 cm and 10 cm, respectively. Compared to the uncooled PV panel, the cooled panel had a distinct enhancement in performance. The efficiency of the PV panel in case #1 was augmented by 5.7% with 50 mm pad thickness and 8.4% for 100 mm pad thickness. Case #2 revealed more improvement in the efficiency by 9% for 5 cm and up to 20% for 10 cm pad thickness. The PV panel electric power was augmented by 7.3% and 13.8% for 2 and 3 lpm water flow rates, respectively. Compared to the flow rate of 1 lpm. The open voltage circuit improved by 4.1% and 9.4% for cases #1 and #2, respectively. The higher air temperature drop was about 11.4 ℃ for case #2 at 10 cm pad thickness.